Tehnike za zagotavljanje veljavnosti in zanesljivosti podatkov v marketinških raziskavah in analiza podatkov v marketingu - Milfelner, Borut (University of Maribor Press, 2023)
Methods for Ensuring the Validity and Reliability of Data in Marketing Research and Marketing Data Analitics. The scientific monograph »Methods for ensuring the validity and reliability of data in marketing research and marketing data analitics« focuses on the collection of data for marketing purposes in organisations and advocates a scientific approach to the measurement of marketing concepts. It justifies the scientific principles of quantitative measurement in marketing to ensure accurate and reliable data and methods for data analysis in marketing. Advanced data analysis techniques such as structural equation modelling, which measure the effects of latent variables that can act as dependent as well as independent variables, are also discussed. The monograph contains seven chapters covering understanding the marketing information system, market orientation, measurement theory in marketing, validity and reliability of measurement scales, methods for testing relationships between parametric and non-parametric variables, and structural equation modelling.